A Case Report Gonadal Hypoplasia Co-Existence With Mullerian Agenesis In 46,XX Female - Heri Farnas; Dedy Hendry (Syntax Literate, 2022)
Introduction: The association or Co-existence of gonadal hypoplasia and Mullerian agenesis is a very rare case. Case Report: We report a 26-year-old phenotypical female presented with primary amenorrhea and underdeveloped secondary sexual characteristics. The hormonal evaluation revealed hypogonadotropic hypogonadismHer karyotype was 46, XX. Diagnostic laparoscopy of the pelvis revealed hypoplasia of the uterine, fallopian tubes, and bilateral ovaries. There were no other morphological malformations. Conclusion: The pathogenesis of the association of Gonadal Hypoplasia Coexistence with Mullerian Agenesis is still mysterious. The treatment is based essentially on hormone substitution therapy and surgical procedure to create neo-vagina for sexual function. The fertility prognosis is unfortunately compromised.